Model catalytic studies of liquid organic hydrogen carriers: Dehydrogenation and decomposition mechanisms of dodecahydro-n-ethylcarbazole on pt(111) - Amende, Maximilian; Gleichweit, Christoph; Werner, Kristin; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Papp, Christian; Koch, Marcus; Wasserscheid, Peter; Laurin, Mathias; Steinrück, Hans-Peter; et al. (ACS Catalysis, 2014)
Liquid organic hydrogen carriers (LOHC) are compounds that enable chemical energy storage through reversible hydrogenation. They are considered a promising technology to decouple energy production and consumption by combining high-energy densities with easy handling. A prominent LOHC is N-ethylcarbazole (NEC), which is reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H -NEC). We studied the reaction of H-NEC on Pt(111) under ultrahigh vacuum (UHV) conditions by applying infrared reflection-absorption spectroscopy, synchrotron radiation-based high resolution X-ray photoelectron spectroscopy, and temperature-programmed molecular beam methods. We show that molecular adsorption of H-NEC on Pt(111) occurs at temperatures between 173 and 223 K, followed by initial C-H bond activation in direct proximity to the N atom. As the first stable dehydrogenation product, we identify octahydro-N-ethylcarbazole (H -NEC). Dehydrogenation to H-NEC occurs slowly between 223 and 273 K and much faster above 273 K. Stepwise dehydrogenation to NEC proceeds while heating to 380 K. An undesired side reaction, C-N bond scission, was observed above 390 K. H-NEC and H-carbazole are the dominant products desorbing from the surface. Desorption occurs at higher temperatures than H-NEC formation. We show that desorption and dehydrogenation activity are directly linked to the number of adsorption sites being blocked by reaction intermediates. © 2014 American Chemical Society.